RESPON PERKECAMBAHAN BENIH PADI (Oryza sativa L.) VARIETAS LOKAL KABUPATEN PADANG PARIAMAN HASIL IRADIASI SINAR GAMMA - Henny Puspita Sari; Fatardho Zudri; Winda Purnama Sari (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Gamma ray irradiation is a mutagenesis method used to obtain new genetic variations in plants, including rice. Local varieties were chosen because they have good adaptability to the local environment and can play an important role in increasing agricultural productivity. The local varieties of rice seeds from Padang Pariaman Regency used in the research were "Madang Pulau", "Putiah Papanai" and "Banang Kuniang". The irradiation doses used were 100 Gy, 200 Gy, 300 Gy, 400 Gy, 500 Gy and 600 Gy. Seeds without irradiation were also used as controls. The results showed that the germination response of local varieties of rice seeds to gamma ray irradiation varied depending on the dose given. In terms of germination percentage, the irradiation dose of 100 Gy showed a significant increase compared to the control in the white Papanai variety. However, irradiation doses of 200 Gy and 300 Gy caused a significant reduction in germination percentage compared with the control. Apart from that, observations were also made on other parameters such as seedling height and root length. The results showed that at irradiation doses of 100 Gy, 200 Gy and 300 Gy, there was a significant reduction in these parameters. Based on these findings, it can be concluded that the use of gamma rays as an irradiation method can influence the germination response of local varieties of rice seeds in Padang Pariaman Regency differently depending on the dose and the variety used.